PROFIL PENGGUNAAN OBAT ANTIVIRUS COVID-19 DI RSUD dr. MURJANI-SAMPIT - Etik Suryanti; Abdul Rahem; Anita Purnamayanti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). The World Health Organization (WHO) until now still defines Covid-19 as a global pandemic where this pandemic is the cause of the biggest public health crisis in this century. RSUD dr. Murjani-Sampit uses several antivirals, including Oseltamivir 75 mg, Favipiravir 200 mg, Remdesivir 200 mg. The purpose of this study was to determine the antiviral profile given to covid-19 patients at dr. Murjani-Sampit. This study used a total sample of hospitalized patients who were given COVID-19 antiviral therapy in the period August 2021. This research method used an observational research design with retrospective sampling. Data collection techniques based on observation of patient prescription data recorded in the pharmacy installation management information system of RSUD dr. Murjani-Sampit. The analytical method used is descriptive analysis with the most data on the use of antiviral drugs and the average percentage for the period August 2021 at dr. Murjani-Sampit which opened 275 patients. The results showed that the most widely administered antivirals were favipiravir 200 mg in 249 patients (90.54%), remdesivir 200 mg in 17 patients (6.18%) and oseltamivir as adjuvant or additional therapy due to influenza in 9 patients (3.27%). The conclusion of this study is that the antivirals used include oseltamivir 75 mg 3.27%, favipiravir 200 mg 90.54%, and remdesivir 200 mg 6.18%.